Impact du relief et des circuits semenciers locaux sur la diversité agro-morphologique du blé dur (Triticum turgidum ssp. durum) dans la vallée d’Er Rich – Imilchil (Maroc) - Ali SAHRI; Lamyae CHENTOUFI; Mustapha ARBAOUI; Marie-Helene MULLER; Pierre ROUMET; Loubna BELQADI (Revue Marocaine des Sciences Agronomiques et Vétérinaires, 2014)
Phenotypic diversity of 101 durum wheat landrace populations collected from the oasis of the Oriental Atlas Mountains (Morocco) was studied. Nine characters (morphological and agronomic) were measured on the 3030 lines (30 lines per population). The frequencies of each phenotypic class were used for the estimate and the analysis of diversity, by considering the geographical zones of origin and the gradients of altitude. The Shannon-Weaver diversity index (H’) showed a wide variability for all considered traits. This index varies from one area to another and from one altitudinal class to another. The mean H’ recorded for all areas was 0.62, indicating the presence of a high degree of polymorphism among the studied durum wheat landrace populations. The results of the multiple component analysis and the hierarchical clustering showed that the geographical proximity and altitude play a main function in the discrimination and the structure of the studied durum wheat populations. The information gathered from this study could be used in conventional breeding programs and in situ conservation of the diversity.